1994
DOI: 10.1128/jb.176.7.2090-2095.1994
|View full text |Cite
|
Sign up to set email alerts
|

Development of a gene cloning system for Streptomyces hygroscopicus subsp. yingchengensis, a producer of three useful antifungal compounds, by elimination of three barriers to DNA transfer

Abstract: Streptomyces hygroscopicus 10-22 could not be transformed with any of the commonly used Streptomyces plasmid vectors and was resistant to plaque formation by the Streptomyces phages phi C31 and R4. Repeated selection resulted in the isolation of derivatives of S. hygroscopicus 10-22 that could be transformed with pIJ101- and pJV1-derived cloning vectors and of restriction-deficient derivatives that could accept DNA propagated in Streptomyces lividans 66. These new strains, which include three that still produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…Interestingly, three putative regulatory genes were identified, with two at the end of, and one flanking, the cluster. Since S. hygroscopicus 10-22 is much more difficult to manipulate genetically than S. hygroscopicus 5008 (Pang et al, 2002;Qin et al, 1994), here we used strain 5008 as a model to investigate the roles of these three regulatory genes in the biosynthesis of cyclothiazomycin. We proved that the cluster is functional in S. hygroscopicus 5008 and we showed that one of the regulatory genes, SHJG8833, is essential for cyclothiazomycin biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, three putative regulatory genes were identified, with two at the end of, and one flanking, the cluster. Since S. hygroscopicus 10-22 is much more difficult to manipulate genetically than S. hygroscopicus 5008 (Pang et al, 2002;Qin et al, 1994), here we used strain 5008 as a model to investigate the roles of these three regulatory genes in the biosynthesis of cyclothiazomycin. We proved that the cluster is functional in S. hygroscopicus 5008 and we showed that one of the regulatory genes, SHJG8833, is essential for cyclothiazomycin biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…A 1-kb supercoiled DNA ladder was used as a size marker. a pSLA2 circular plasmids were introduced into ZX7, and thiostrepton-resistant colonies were inoculated into CM medium containing thiostrepton (23). After 7 days at 30°C, spores were streaked on CM plates without selection for 7 days at the same temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Culture and transformation of Streptomyces followed the methods of Kieser et al (16). To obtain good sporulation, strain ZX7 grew on complete medium (23). Plasmid pLUS450, kindly provided by Carton Chen, contained 2.6-kb chromosomal telomere sequences.…”
Section: Methodsmentioning
confidence: 99%
“…Microbiological and genetic manipulations in Escherichia coli and Streptomyces were according to Kieser et al (2000). Five solid media were used for culturing Streptomyces strains: NE (per litre: 10 g glucose, 2 g yeast extract, 2 g Casamino acids, 1 g beef extract, 15 g agar, pH 7.0) (Thiara & Cundliffe, 1995), PYM (per litre: 5 g peptone, 3 g yeast extract, 3 g malt extract, 10 g glucose, 20 g agar), LB, R5 (Kieser et al, 2000) and HAUCM (Qin et al, 1994). Dot-blot hybridization.…”
Section: Methodsmentioning
confidence: 99%